This I Believe - Pregel, Boris (Tufts Archival Research Center, 2006)
Boris Pregel, President of Canadian Radium and Uranium Corporation, relates some of his experiences in Europe up to World War II to explain why charity, altruism and selflessness areso vital to his personal beliefs and adds that it is also important to live by ones beliefs to maintain dignity.